2016
DOI: 10.1016/j.chemosphere.2016.03.109
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability and aquatic toxicity of quaternary ammonium-based gemini surfactants: Effect of the spacer on their ecological properties

Abstract: Aerobic biodegradability and aquatic toxicity of five types of quaternary ammonium-based gemini surfactants have been examined. The effect of the spacer structure and the head group polarity on the ecological properties of a series of dimeric dodecyl ammonium surfactants has been investigated. Standard tests for ready biodegradability assessment (OECD 310) were conducted for C12 alkyl chain gemini surfactants containing oxygen, nitrogen or a benzene ring in the spacer linkage and/or a hydroxyethyl group attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 39 publications
3
58
1
Order By: Relevance
“…The second product ion results from the loss of the terminal lysine amino acid residue (observed at m/z 129.10 (b 2 )) by amide bond cleavage forming a doubly charged product ion (10) at m/z 474.49. Elimination of the pipecolic acid part of ion (9) also leads to the formation of ion (10), which subsequently dissociates by eliminating the last terminal lysine, forming ion (11) observed at m/z 410.44. Furthermore, ion (10) loses the tail region and the attached head forming the previously mentioned singly and doubly charged ions designated as (4) and (4 0 ).…”
Section: Dissociation Of Product Ion (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…The second product ion results from the loss of the terminal lysine amino acid residue (observed at m/z 129.10 (b 2 )) by amide bond cleavage forming a doubly charged product ion (10) at m/z 474.49. Elimination of the pipecolic acid part of ion (9) also leads to the formation of ion (10), which subsequently dissociates by eliminating the last terminal lysine, forming ion (11) observed at m/z 410.44. Furthermore, ion (10) loses the tail region and the attached head forming the previously mentioned singly and doubly charged ions designated as (4) and (4 0 ).…”
Section: Dissociation Of Product Ion (B)mentioning
confidence: 99%
“… In fact, Badea et al reported threefold increase in topical transgene expression in animals treated with N , N ′‐bis(dimethylhexadecyl)‐1,3‐propanediammonium dibromide (designated as 16‐3‐16) gemini surfactant‐based nanoparticles compared with animals treated with naked DNA . Despite the success of the traditional gemini surfactants, concerns regarding their toxicity have arisen . Several approaches have been undertaken to address this problem, including the insertion of biocompatible and biodegradable moieties such as sugars, lipids and amino acids .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia et al, 2016 investigated biodegradability and aquatic toxicity of quaternary ammonium-based gemini surfactants and found that these surfactants are less toxic to the aquatic life than the monomeric ones. Furthermore, the aquatic toxicity can be reduced by increasing the hydrophilicity of the surfactant molecule by including a heteroatom in the spacer or replacing a methyl by a hydroxyethyl group in the ammonium polar head group (Garcia et al, 2016).…”
Section: Toxicity Of Surfactantsmentioning
confidence: 99%
“…An ever increasing attention is paid to problems related to post-incident waste of foaming agents. These agents, due to the surfactants contained in them, may have an adverse effect on the environment [2][3][4][5][6][7][8][9][10]. One of the solutions enabling an easy and safe removal of hazardous substances is the use of sorbents, which, depending on their bulk density, can be used both in land and water actions [11].…”
Section: Introductionmentioning
confidence: 99%